Uji Sitotoksik Fraksi n-Heksana, Etil Asetat, Etanol dari Ekstrak Etanolik Daun Ende (Coccinia grandis (L.) Voigt) pada Sel HeLa - NURAINI HARMASTUTI; GUNAWAN PAMUDJI WIDODO; MARIA E.D.O. HUREK MAKING; MARIA YANGSYE LENGGU; FEOLISTIN MIENCE POBAS (Fakultas Farmasi Universitas Setia Budi, 2012)
Ende leaf (Coccinia grandis (L.) Voigt) is the one of plant that most popular in Nusa Tenggara Timur province. The study was aimed to know the cytotoxic effect of n-hexane, ethyl acetate, and ethanol fractions from ethanolic extract of ende leaf on hela cell and its IC50 value. Dried ende was macerated with 96 % ethanol solvent, then it was fractionated by n-hexane, ethyl acetate, and ethanol solvent. Then it was tested the cytotoxic by MTT (Microculture Tetrazolium Salt) method on HeLa cell The absorbance response was converted into abbreviation of cell viability. IC50 value was calculated with linear regression equation between logarithm of concentration samples versus percentage viability of HeLa cell. The result showed that the cytotoxic test of ende leaf against HeLa cell presented the IC50 value of ethanolic extract and n-hexane, ethyl acetate, and ethanol fractions were 415.719 ppm; 307.142 ppm; 50303.71 ppm; dan 50722.424 ppm, respectively.